Could zoledronic acid prevent root resorption in replanted rat molar?. Issue 6 (7th July 2015) - Yoo, Jung Eun; Kim, Mi Sun; Kwon, Yong–dae; Kim, Eun‐Cheol; Kim, Kwang Chul; Choi, Sung Chul
Abstract: Background/Aim: In this study, we evaluated whether zoledronate could suppress the progression of external root resorption in rat due to delayed replantation by inhibiting osteoclastic activity. Also, we estimated the optimal dosage of zoledronate in root treatment of the rat model for a maximum effect of zoledronate. Material and methods: Maxillary first molars in Sprague Dawley rats ( N  = 84) were extracted, dried for 60 min, and then replanted. The rats were divided into 6 groups (1 mM alendronate, and 1, 5, 10, 20, 40 μM zoledronate). At 4 and 8 weeks postreplantation, the animals were sacrificed and evaluated by radiographic and histological analysis. Results and Conclusion: There were no significant differences at 4 weeks. However, at 8 weeks, 10, 20, and 40 μM ZOL showed more increased radiopaque and smaller periapical lesion in radiographic analysis. In histological analysis, all groups showed similar inflammatory root resorption rate at 4 weeks. However, at 8 weeks, 20 and 40 μM ZOL showed lower rate than those of other groups ( P  < 0.05). In concerning of replacement resorption, there were no significant differences statistically. In this animal experiment, zoledronate was capable of limiting the occurrence of root resorption in delayed replantation model. In particular, 20 μM dosage of zoledronate solution showed the most effective dose in long‐term follow up and might be suitable for inhibition of root resorption in delayed tooth replantation.